Обратимая ползучесть силикатных материалов в воде - Лордкипанидзе, М.; Парцхаладзе, Г. (Інститут фізики гірничих процесів НАН України, 2009)
Аналізуються експериментальні дані оборотної повзучості бетону та скла у сухому та водонасиченому стані, оброблені спеціальною комп’ютерною програмою. A new phenomenon has been discovered and further investigated in a number of solid bodies of dissimilar nature, in particular, in silicate materials. It involves a gradual development of additional deformation, dying out with time, in a solid body specimen subjected to constant load, with a suitable surface-active agent applied on the surface area (water on mineral substances). The removal of the surface-active agent leads to a gradual reappearance of the deformation, with the specimen regaining its original state of elastic stress.